POLITICAL LEGAL RECONSTRUCTION OF POPULATION ADMINISTRATION LAW IN MEASURING THE CONSTITUTIONAL EXISTENCE OF CONTEMPORARY NUSANTARA BELIEF ADHERENTS - ., Suratman; Anggraini, Lestari; Madya Putri, Yessy (Jurnal Meta-Yuridis, 2026)
Recognition of indigenous belief adherents in Indonesia is an essential part of the state’s efforts to ensure the fulfillment of citizens’ constitutional rights. For decades, followers of local beliefs have faced administrative barriers because the population administration system only accommodated officially recognized religions. This condition has resulted in various forms of discrimination in accessing public services, such as marriage registration, education, and other social services. This study employs a normative legal research method with statutory and conceptual approaches, using qualitative analysis of primary, secondary, and tertiary legal materials. The discussion shows that Constitutional Court Decision No. 97/PUU-XIV/2016 marked a significant turning point in transforming the paradigm of Population Administration Law by recognizing the identity of belief adherents in official state documents, such as electronic identity cards (KTP-el) and Family Cards. The decision has encouraged more inclusive population administration policies through identity inclusion and data integration in the Population Administration Information System (SIAK), providing legal certainty for belief adherents in accessing public services. However, in practice, administrative and social constraints still exist, including limited bureaucratic capacity and societal stigma toward belief adherents